2019
DOI: 10.3390/cancers11122038
|View full text |Cite
|
Sign up to set email alerts
|

GSTO1*CC Genotype (rs4925) Predicts Shorter Survival in Clear Cell Renal Cell Carcinoma Male Patients

Abstract: Omega class glutathione transferases, GSTO1-1 and GSTO2-2, exhibit different activities involved in regulation of inflammation, apoptosis and redox homeostasis. We investigated the the prognostic significance of GSTO1 (rs4925) and GSTO2 (rs156697 and rs2297235) polymorphisms in clear cell renal cell carcinoma (ccRCC) patients. GSTO1-1 and GSTO2-2 expression and phosphorylation status of phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt)/ /mammalian target of rapamycin (mTOR) and Raf/MEK/extracellular sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 54 publications
(55 reference statements)
1
13
0
Order By: Relevance
“…With the development of clinical management of ccRCC, several prognostic factors, such as tumor grade and stage, tumor size, and tumor number, are well characterized. However, ccRCC has complex genetic and molecular alterations [24], which could affect the biological processes, and some of the biological processes are closely associated with the prognosis of ccRCC patients, such as autophagy [25], ferroptosis [15], and redox [26]. Most of these commonly used prognostic factors do not consider either genetic and molecular alterations or dysregulated biological processes, and it made these commonly used prognostic factors not perfect for accurate prognostic prediction of ccRCC patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…With the development of clinical management of ccRCC, several prognostic factors, such as tumor grade and stage, tumor size, and tumor number, are well characterized. However, ccRCC has complex genetic and molecular alterations [24], which could affect the biological processes, and some of the biological processes are closely associated with the prognosis of ccRCC patients, such as autophagy [25], ferroptosis [15], and redox [26]. Most of these commonly used prognostic factors do not consider either genetic and molecular alterations or dysregulated biological processes, and it made these commonly used prognostic factors not perfect for accurate prognostic prediction of ccRCC patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further investigations into the mechanism underlying NSCLC development and progression are essential for improving the treatment of NSCLC. The expression levels of GSTO1 were previously discovered to be upregulated in various types of cancer, including lymphoma, melanoma and colorectal cancer ( 7 , 16 , 21 ). However, to the best of our knowledge, the role of GSTO1 in NSCLC has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Chuang et al (14) illustrated that the expression levels of GSTO1 were upregulated in human bladder cancer cells. Moreover, GSTO1 has been revealed to contribute to cell growth, death, migration and invasion in several types of cancer cell (7,(15)(16)(17). For example, Wang et al (15) reported that GSTO1 was upregulated in cutaneous malignant melanoma (CMM) tissues and cells, where it contributed to CMM cell growth, migration and invasion.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer cells have altered lipid and amino acid metabolic pathways, glycolysis, and redox homeostasis [1,5]. Indeed, altered energy metabolism with upregulated glucose transporter expression, disrupted redox homeostasis with upregulated glutathione transferase (GST) and high telomerase activityare responses that maintain DNA integrity, retaining replication, proliferation and cancer cell resistance [1,5,6]. Chemotherapy has many disadvantages, including drug toxicity, rapid degradation, low specificity and limited targeting.…”
Section: Introductionmentioning
confidence: 99%